Knowing, Learning, and Experiencing: Problems of ELT during Online Classes in Pakistan - Tania Shabir Shaikh; Muhammad Hassan Abbasi (University of Chitral Journal of Linguistics and Literature, 2024)
The Global Pandemic introduced new challenges in pedagogy, methodology, and curriculum. However, it offered some novel solutions for academia to rapidly shift from traditional teacher-centered classrooms to student-oriented interactive classrooms using online tools. Hence, this study aims to identify the technical, institutional, and academic problems English language teachers face during online classes for undergraduate students at a public sector university in Karachi, Pakistan. For this purpose, the study utilized a mixed-method approach, and the target population included sixteen teachers teaching virtually. Data was collected in two stages using purposive sampling through an online teaching form from all the respondents, and to know teachers' experiences while conducting the classes, interviews were conducted. Semi-structured interviews were conducted with five participants. The findings suggest that teachers face problems with ICT skills, digital resources, content development, assessment, and using different online platforms for tasks and activities. The results indicate that teachers also met multiple economic, technological, interaction, attention, motivational, and well-being issues of learners during the online classes. Comparatively, some young teachers reflected the opposite trends and were motivated to explore this new education system. Therefore, the higher education institutes in Pakistan should immediately develop new curricula in alignment with the technological needs. Also, sufficient training for ELT practitioners and teaching language skills must be provided for the betterment of future generations.